‘You never been on a ride like this befo’: Los Angeles, automotive listening, and Dr. Dre’s ‘G-Funk’* - Williams, Justin (Popular Music History, 2010)
Since the 1920s, multiple historically specific factors led to the automobile-saturated environment of Los Angeles, contributing to a car-dependent lifestyle for most of its inhabitants. With car travel as its primary mode of mobility, and as a hub of numerous cultural industries throughout the twentieth century, the city has been the breeding ground for a number of car cultures, including hot rods, custom cars, and lowriders in addition to the large output of films and music recordings produced. In rap music of the early 1990s, producer/rapper Dr. Dre’s (Andre Romelle Young) creation of a style labelled ‘G-funk’, according to him, was created and mixed specifically for listening in car stereo systems. This article provides one case study of music’s intersections with geography, both the influence of urban geography on music production and the geography of particular listening spaces. As borrowing is central to hip-hop’s ethos, Dr. Dre’s production reflects how musical materials become re-used for a new space, updated and customized for the automotive listening experience.